Videogames, libraries, and the feedback loop : learning beyond the stacks - Abrams, Sandra Schamroth; Gerber, Hannah R. (Emerald Publishing Limited, 2021)
Offering a fresh understanding of the learning potential of youth videogaming in public libraries, and delving into research-based accounts which showcase feedback mechanisms that nurture meaningful learning, Abrams and Gerber equip readers to re-envision library programming that specifically features youth videogame play.